ANALISIS PENGARUH PROFESIONALISME PELAUT, KEPUASAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN - Suharso Suharso (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2013)
This research examines about direct and indirect effects of four variables by five hypotheses. Merchant seafarers professionalism to job satisfaction (H1),  professionalism to organizational commitment (H2),  Job satisfaction to organizational commitment (H3), Job satisfaction to personal performance ( H4), and organizational commitment to personal performance (H5). The respondents were the Indonesian merchant seafarers to the amount of 135 people from multidimension. Because of high mobility of merchant seafarers, the sampling method was accidental sampling.  Pre research   was taken by validity and reliability terst using questionares from 40 respondents.The result of research describes respondents’ profile from age, rank, certificate, during sea services, take home pay, last hired company and recent job status. Empirical finding indicates that hypothesis 1 can be proved because estimation parameter between seafarers professionalism and  job satisfaction shows CR+ 1.976 or >2.00. P+ 0.048 level with significancy 0.05 or it indicates positive significant. Hypothesis 2 can be proved  because estimation parameter between professionalism and organizational commitment shows CR= 2.124 and P=0.034 or it indicates positive significant. Hypothesis 3 can be proved because estimation parameter between job satisfaction and organizational commitment shows CR=4.109 and P=0.000.  Hhypothesis 4 can be proved because estimation parameter between job satisfaction and performance shows CR =3.221 and P=0.001. Hypothesis 5 can be proved because estimation between organizational commitment and personal performance shows CR =2.171 atau > 2.00 level with P =0.03 with significancy 0.05 or it indicates positive significant.Based on standardized regresion weight, indicators which have the biggest coeficient are suggested to: building solid teamwork, enhance transfer of knowledge from senior to junior seafarers, arrange rank promotion program in ship, and improve the certainity of vision, mission, and organizational regulation of shipping company. Next research agenda is re-research using purposive sampling.Key words : Professionalism, Indonesian Seafarers Profession, Job satisfaction, Personal Performance.